2018
DOI: 10.3390/molecules23123134
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Suzuki-Miyaura Cross-Coupling of Pentafluorophenyl Esters

Abstract: Although the palladium-catalyzed Suzuki-Miyaura cross-coupling of aryl esters has received significant attention, there is a lack of methods that utilize cheap and readily accessible Pd-phosphane catalysts, and can be routinely carried out with high cross-coupling selectivity. Herein, we report the first general method for the cross-coupling of pentafluorophenyl esters (pentafluorophenyl = pfp) by selective C–O acyl cleavage. The reaction proceeds efficiently using Pd(0)/phosphane catalyst systems. The unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…The pyridine "throw-away" family of ligands render this class of Pd-NHC precatalysts an attractive method due to simplicity of synthesis and high reactivity in C(acyl)-O insertion. Later, we demonstrated that the cross-coupling is effectively promoted at remarkably mild room temperature conditions (Scheme 17C), while supporting various Pd-NHC precatalysts as well as Pd(II)-NHC hydroxide dimers ( Figure 2) In 2018, to further explore the reactivity of phenolic esters in the acyl Suzuki cross-coupling reaction, we have reported the Pd-phosphine-catalyzed cross-coupling of pentafluorophenyl esters (pfp) (Scheme 19) [52]. Due to the activating effect of the fluorine substituents, a mild Pd2(dba)3/PCy3 catalyst was able to effectively activate the C(acyl)-O bond giving products in high yields without the need for a more reactive, albeit less selective, Pd-NHC precatalyst.…”
Section: Suzuki Cross-coupling Of Amidesmentioning
confidence: 84%
See 2 more Smart Citations
“…The pyridine "throw-away" family of ligands render this class of Pd-NHC precatalysts an attractive method due to simplicity of synthesis and high reactivity in C(acyl)-O insertion. Later, we demonstrated that the cross-coupling is effectively promoted at remarkably mild room temperature conditions (Scheme 17C), while supporting various Pd-NHC precatalysts as well as Pd(II)-NHC hydroxide dimers ( Figure 2) In 2018, to further explore the reactivity of phenolic esters in the acyl Suzuki cross-coupling reaction, we have reported the Pd-phosphine-catalyzed cross-coupling of pentafluorophenyl esters (pfp) (Scheme 19) [52]. Due to the activating effect of the fluorine substituents, a mild Pd2(dba)3/PCy3 catalyst was able to effectively activate the C(acyl)-O bond giving products in high yields without the need for a more reactive, albeit less selective, Pd-NHC precatalyst.…”
Section: Suzuki Cross-coupling Of Amidesmentioning
confidence: 84%
“…Due to the activating effect of the fluorine substituents, a mild Pd2(dba)3/PCy3 catalyst was able to effectively activate the C(acyl)-O bond giving products in high yields without the need for a more reactive, albeit less selective, Pd-NHC precatalyst. In 2018, to further explore the reactivity of phenolic esters in the acyl Suzuki cross-coupling reaction, we have reported the Pd-phosphine-catalyzed cross-coupling of pentafluorophenyl esters (pfp) (Scheme 19) [52]. Due to the activating effect of the fluorine substituents, a mild Pd2(dba)3/PCy3 catalyst was able to effectively activate the C(acyl)-O bond giving products in high yields without the need for a more reactive, albeit less selective, Pd-NHC precatalyst.…”
Section: Suzuki Cross-coupling Of Estersmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, these reagents are more selective than "fully perpendicular" (τ = 88.6 • ) N-acyl-glutarimides (Scheme 4A). Importantly, full selectivity in the cross-coupling of N-acylphthalimides in the presence of electronically activated pfp esters (pfp = pentafluorophenyl) was observed (Scheme 4B) [50]. This further confirms the unique activation platform of the amide bond, wherein the selectivity is tuned by both sterics and electronics of N-substituents, which, for obvious reasons, is not possible with other acyl electrophiles.…”
Section: Resultsmentioning
confidence: 53%
“…We became interested in developing the iron-catalyzed cross-coupling of aryl chlorobenzoates as part of our program in iron catalysis [36][37][38][39][40][41][42][43] and the cross-coupling of C(acyl)-X (X = N, O) electrophiles [44,45]. Recently, several groups have reported methods for the nickel and palladium-catalyzed C(acyl)-O bond activation of aryl benzoates, leading to the selective formation of acyl-metal intermediates (Scheme 2, box) [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. While aryl benzoates have long been established as electrophiles in nucleophilic addition to the ester bond via tetrahedral intermediates owing to the increased electrophilicity of the ester bond due to O lp to Ar conjugation [65], the recent advances in accessing acyl metals from aryl benzoates significantly expand the utility of this class of carboxylic acid derivatives in organic synthesis.…”
Section: Resultsmentioning
confidence: 99%